Kissing-loop nano-kirigami structures with asymmetric transmission and anomalous reflection - Yingying Chen; Qinghua Liang; Haozhe Sun; Xiaochen Zhang; Weikang Dong; Meihua Niu; Yanji Zheng; Yanjie Chen; Cuicui Lu; Lingling Huang; Xiaowei Li; Lan Jiang; et al. (Light: Advanced Manufacturing)
Nano-kirigami technology enables the flexible transformation of two-dimensional (2D) micro/nanoscale structures into three-dimensional (3D) structures with either open-loop or close-loop topological morphologies, and has aroused significant interest in the fields of nanophotonics and optoelectronics. Here, we propose an innovative kissing-loop nano-kirigami strategy, wherein 2D open-loop structures can transform into 3D kissing-loop structures while retaining advantages such as large deformation heights and multiple optical modulations. Benefited from the unidirectional deformation of the structures, the kissing-loop nano-kirigami exhibits significant asymmetric transmission under x-polarized light incidence. Importantly, the Pancharatnam-Berry geometric phase is experimentally realized in nano-kirigami structures for the first time, resulting in broadband anomalous reflection in the near-infrared wavelength region. The kissing-loop nano-kirigami strategy can expand the existing platform of micro/nanoscale fabrication and provide an effective method for developing optical sensing, spatial light modulations, and optoelectronic devices.